First record of the Granulate Ambrosia Beetle, Xylosandrus crassiusculus (Coleoptera: Curculionidae, Scolytinae), in the Iberian Peninsula - Gallego, Diego; Lencina, José Luis; Mas, Hugo; Ceveró, Julia; Faccoli, Massimo (Zootaxa, 2017)
The Granulate Ambrosia Beetle Xylosandrus crassiusculus, an alien species of Asian origin, was recorded for first time in the Iberian Peninsula. Many specimens were collected in October 2016 in the Valencia region (Spain) from infested carob trees. The species is included in the EPPO Alert List as causing serious damage in many Mediterranean regions. A key for the morphological identification of the Xylosandrus species occurring in Europe is also reported.